Uterine artery embolization: the only life saving measure in some obstetric cases - Gokhale, Asha N.; Chawla, Latika J.; Khajindar, Shridhar (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Uterine artery embolization is a highly specialised and efficacious method that can be used prophylactically to reduce obstetric haemorrhage. Its use in modern obstetrics is currently limited to morbidly adherent placenta and acreta. This report presents a case where uterine artery embolization has been used as the primary treatment for obstetric haemorrhage in a patient with high risk for PPH where surgical management would not have been possible. We aim at highlighting the benefits of this procedure in terms of reduced surgical blood loss, morbidity and fertility preservation.